2015
DOI: 10.1016/j.jfma.2013.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Ozone therapy in the management and prevention of caries

Abstract: The purpose of this article was to assess the effectiveness of ozone therapy in the management and prevention of caries, reviewing clinical and in vitro studies. Ozone has proven to be effective against gram-negative and gram-positive bacteria, viruses, and fungi. In dentistry, most of the published articles are based on ozone's antimicrobial effects and the treatment of caries. Most of the clinical studies reported ozone to be a promising alternative to conventional methods for caries management. However, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 42 publications
0
39
0
12
Order By: Relevance
“…Notably, ozone can also sterilize both gram positive bacteria and gram-negative bacteria. 17 Furthermore, ozone off ers other advantages such as improved wound healing, enhanced immune function, and serves as an environmentally-friendly and high effi cacy treatment modality. 6 Greatly enhancing its clinical accessibility, ozone gas is now available in an oxygen solution.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ozone can also sterilize both gram positive bacteria and gram-negative bacteria. 17 Furthermore, ozone off ers other advantages such as improved wound healing, enhanced immune function, and serves as an environmentally-friendly and high effi cacy treatment modality. 6 Greatly enhancing its clinical accessibility, ozone gas is now available in an oxygen solution.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone therapy has been used to treat different conditions as summarized in Table 1, seen in different Randomized Clinical Trial (RCT) and reviewed by many authors. The conditions already studied includes: Tissue healing from inflammatory processes showed by a systematic review that included only RCT for chronic wounds (Fitzpatrick et al, 2018) and revised by Travagli et al (2010) and Valacchi et al (2005); for back pain revised by Braidy et al, 2018 and also showed by Andrade et al (2019) in a RCT; osteoarthritis showed in a systematic reviews (Anzolin and Bertol, 2018;Noori-Zadeh et al, 2019) and seeing in an RCT (Babaei-Ghazani et al, 2018; Lopes de Jesus et al, 2017) and in a clinical trial phase 2 (Calunga et al, 2012); diabetic foot ulcers as showed by a RCT (Zhang et al, 2014) and revised by others (Braidy et al, 2018); dental problems such as caries and periodontitis summarized in a review (Almaz and Sönmez, 2015); in the treatment of systemic sclerosis, as seeing in a RCT (Hassanien et al, 2018); multiple sclerosis, seeing in a clinical trial phase 1 (Delgado-Roche et al, 2017; Nowicka, 2017); among other conditions showed in clinical trials (Vanni et al, 2016). Increase in vessel numbers, collagen deposition and myofibroblasts numbers; Stimulation of the growth factors and peroxide releases; Improvement in oxygenation of the affected area.…”
Section: Ozone Clinical Usesmentioning
confidence: 99%
“…Ozone is a good antioxidative and very effective in antibiotic resistant strains with accelerated efficiency in acidic pH environment [18]. It is administered on patients for therapeutic purposes in various forms like gaseous ozone, as an aqueous solution, oil or as ozonated water [16,19]. Kist, et al suggested that ozone gas might be a possible alternative disinfection agent within the root canal treatment of apical periodontitis based on the results of a clinical trial [20].…”
Section: Experimental Designmentioning
confidence: 99%